2021
DOI: 10.1094/mpmi-04-21-0078-r
|View full text |Cite
|
Sign up to set email alerts
|

Trigger and Suppression of Antiviral Defenses by Grapevine Pinot Gris Virus (GPGV): Novel Insights into Virus-Host Interaction

Abstract: Grapevine Pinot gris virus (GPGV) is an emerging trichovirus that has been putatively associated with a novel grapevine disease known as grapevine leaf mottling and deformation (GLMD). Yet the role of GPGV in GLMD disease is poorly understood since it has been detected both in symptomatic and symptomless grapevines. We exploited a recently constructed GPGV infectious clone (pRI::GPGV-vir) to induce an antiviral response in Nicotiana benthamiana plants. In silico prediction of virus-derived small interfering RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…This observation prompted investigations into the onset of recovery in GPGV‐infected plants in relation to the activation of antiviral RNA silencing involved in GPGV infection. Hence, when in a subsequent study an infectious clone of GPGV (pRI::GPGV‐vir) was inoculated in wild‐type and transgenic (16c line) N. benthamiana plants, in silico prediction of virus‐derived small interfering RNAs (vsiRNAs) and gene expression analyses revealed the involvement of Dicer‐like 4 ( DCL4 ), Argonaute protein 5 ( AGO5 ) and RNA‐dependent RNA polymerase 6 ( RDR6 ) genes during GPGV infection, suggesting the activation of the posttranscriptional gene‐silencing (PTGS) pathway as a plant antiviral defence (Tarquini, Pagliari, et al, 2021). Thus, the observed attenuation or disappearance of disease symptoms in GPGV‐infected grapevines may be explained by the well‐established association between the activation of the PTGS pathway and the onset of symptom recovery (Ghoshal & Sanfaçon, 2015; Kørner et al, 2018; Križnik et al, 2020; Smith et al, 2011).…”
Section: The Symptomatic/asymptomatic Puzzlementioning
confidence: 99%
See 4 more Smart Citations
“…This observation prompted investigations into the onset of recovery in GPGV‐infected plants in relation to the activation of antiviral RNA silencing involved in GPGV infection. Hence, when in a subsequent study an infectious clone of GPGV (pRI::GPGV‐vir) was inoculated in wild‐type and transgenic (16c line) N. benthamiana plants, in silico prediction of virus‐derived small interfering RNAs (vsiRNAs) and gene expression analyses revealed the involvement of Dicer‐like 4 ( DCL4 ), Argonaute protein 5 ( AGO5 ) and RNA‐dependent RNA polymerase 6 ( RDR6 ) genes during GPGV infection, suggesting the activation of the posttranscriptional gene‐silencing (PTGS) pathway as a plant antiviral defence (Tarquini, Pagliari, et al, 2021). Thus, the observed attenuation or disappearance of disease symptoms in GPGV‐infected grapevines may be explained by the well‐established association between the activation of the PTGS pathway and the onset of symptom recovery (Ghoshal & Sanfaçon, 2015; Kørner et al, 2018; Križnik et al, 2020; Smith et al, 2011).…”
Section: The Symptomatic/asymptomatic Puzzlementioning
confidence: 99%
“…Indeed, Tarquini, Pagliari, et al (2021) demonstrated the ability of GPGV to suppress the antiviral PTGS in transgenic (16c line) N . benthamiana plants by assessing the expression level of green fluorescent protein (GFP) in 16c plants and by quantifying GFP ‐derived small interfering RNAs (siRNAs) using stem‐loop primers.…”
Section: The Symptomatic/asymptomatic Puzzlementioning
confidence: 99%
See 3 more Smart Citations